Tele-simulation in nutrition and dietetics students, impact on learning and perception: a study pilot - Piñuñuri, Raúl; Muñoz-Castillo, Catalina; Herrera-Aliaga, Eduardo; Rodríguez-Palleres, Ximena; Pino-Astorga, Carolina; Estrada, Lisbell D. (Frontiers in Education, 2023)
Introduction During the COVID-19 pandemic, tele-simulation emerged as an educational alternative, being useful for the development of Nutritional Care Process (NCP) skills. The importance of this study lies in knowing the impact of tele-simulation on perception and learning for the NCP. The aim of this research was to know the academic performance and the student’s perception of their ability to apply a dietary anamnesis. Materials and methods A quantitative, longitudinal, three-temporal study was conducted with a purposive sample of 25 Nutrition and Dietetics students during 2021. All students performed three tele-simulations with a standardized patient, in relation to the NCP. Results The mean response among the three tele-simulations developed on perception in tele-simulation with a standardized patient was 4.6 (Scale 1–5). The aspect with the best perception of the students was observed in relation to the feasibility and viability of the tele-simulation. The students improved in disciplinary aspects such as the investigation of the culinary technique, representativeness and quantification of the intake through the application of the NCP. Conclusion Tele-simulation with standardized patient is viable as a teaching-learning methodology for the application of the PNC. It is possible to demonstrate a higher performance in the nutritional interview.